Lokasi Alternatif TPS 3R (Studi; Kelurahan Purwokerto Kulon, Kabupaten Banyumas) - Chahya Chairani; Dwi Nowo Martono; Sri Wahyono (Jurnal Penelitian Pendidikan IPA, 2023)
Purwokerto is planning to build Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS 3R) in each of its villages, this is due to minimize the quantity of waste that will be transported to Tempat Pembuangan Akhir (TPA), 12 TPS 3R have been built in 12 urban villages ini this city. South Purwoketo Subdistrict only has 1 TPS 3R in 1 village while there are 6 village that do not yet have TPS 3R, so the location of this research is in Purwokerto Kulon which is close to the activity center of Purwokerto. This study aims to find an alternative location for TPS 3R in Kelurahan Purwokerto Kulon. The method used in this study uses the AHP method and Spatial Analysis. This study resulted in locations that were â€œVery Appropriateâ€, â€œSufficiently Appropriateâ€ and â€œNot Appropriateâ€. There are 3 alternative location points with the "Very Appropriate" category to build TPS 3R in Purwokerto Kulon. These 3 locations are in the middle of the Purwokerto Kulon Village area, these 3 locations are on vacant land with a land area of >200 mÂ² with a slope of 0% - 8% or flat, located > 200 m from a body of water/river and these three locations located in an area with minimal human activity. These three alternative locations are able to serve in waste processing in Purwokerto Kulon Village because their placement is close to the service area within a radius of no more than 1 Km